The theory of everything : quantum and relativity is everywhere - a Fermat universe - Schwarzer, Norbert (Singapore : Pan Stanford Publishing, 2018)
"The book unifies quantum theory and the general theory of relativity. As an unsolved problem for about 100 years and influencing so many fields, this is probably of some importance to the scientific community. Examples like Higgs field, limit to classical Dirac and Klein-Gordon or Schrödinger cases, quantized Schwarzschild, Kerr, Kerr-Newman objects, and the photon are considered for illustration. An interesting explanation for the asymmetry of matter and antimatter in the early universe was found while quantizing the Schwarzschild metric. Along the way, the methods outlined in the book are also used to tackle the problem of the proof of Fermat's last theorem, as there is a connection between quantum theory and basic mathematical laws of integers. The book shows that the proof of Fermat's last theorem can be brought down to a few lines by applying new quantum theoretical methods. Because such proof was sought for over 370 years, this book is of definite interest to mathematicians."--Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Quantum theory; MATHEMATICS / Algebra / General; MATHEMATICS / Probability & Statistics / General; SCIENCE / Quantum Theory